2009
DOI: 10.1007/s12078-009-9043-7
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory, Olfactory and Trigeminal Interactions in a Model Carbonated Beverage

Abstract: Flavour results from the integration of aroma, taste and chemosensory information within the brain. Understanding interactions between the anatomically separate systems which relay this information is crucial to our appreciation of how different aspects of food contribute to flavour perception and the formulation of successful products. To examine these interactions, a beverage system was created containing elements capable of stimulating gustatory, olfactory and trigeminal systems. Using ingredients relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 46 publications
8
71
1
Order By: Relevance
“…It is theorized that chemesthetic stimuli such as carbonation excite peripheral sensory receptors and activate sensory fibers in the NTS of the brainstem, which is the main structure responsible for swallow initiation [16,17,19,[45][46][47][48][49][50][51]. Although in the present study CTL did not elicit a faster swallowing response, it did significantly decrease penetration and aspiration compared to NCTL.…”
Section: Resultscontrasting
confidence: 71%
“…It is theorized that chemesthetic stimuli such as carbonation excite peripheral sensory receptors and activate sensory fibers in the NTS of the brainstem, which is the main structure responsible for swallow initiation [16,17,19,[45][46][47][48][49][50][51]. Although in the present study CTL did not elicit a faster swallowing response, it did significantly decrease penetration and aspiration compared to NCTL.…”
Section: Resultscontrasting
confidence: 71%
“…This could be due to further perceptual interactions between bitterness and trigeminal sensations in the oral cavity associated with the hop aroma, since the perceived increased bitterness intensity at this level cannot be due to olfaction. Taste-trigeminal interactions have been re-ported previously in beverages (Hewson et al, 2009). …”
Section: Impact Of Hop Aroma On Perceived Bitterness Intensitymentioning
confidence: 79%
“…The role of congruency on the observed level of taste-aroma interactions is inconsistent; some researchers only observed additivity in congruent taste-aroma pairs (Dalton et al, 2000;Labbe, Damevin, Vaccher, Morgenegg, & Martin, 2006), while others have reported additivity in taste-aroma pair irrespective of congruency (Delwiche & Heffelfinger, 2005). Although both taste and trigeminal sensations are sensed by distinct sensory systems, interactions exist between them which can also affect the perception of flavour in foods (Hewson, Hollowood, Chandra, & Hort, 2009). Trigeminal sensations involve the perception of texture, pungency and temperature within the oral cavity, nasal cavity or on the tongue (Cullen & Leopold, 1999).…”
mentioning
confidence: 99%
“…Samples were made up to 1 L with water and left to solubilise on a roller bed for >6 h and then chilled at 6˚C. The CO 2 containing samples were carbonated to ~3.6 volumes following a method previously described by Hewson 7 . For samples containing hop acids, 100 ”L of the hop acid stock was added directly to empty 40 mL sample vials (Fisher Scientific, Loughborough, UK) to create a final sample concentration of 480 ”L/L Tetrahop and 120 ”L/L Redihop, resulting in 600 ”L/L total hop acid concentration (IBU ~80).…”
Section: Samplesmentioning
confidence: 99%